Westward tilt of low‐latitude plasma blobs as observed by the Swarm constellation. Issue 4 (22nd April 2015) - Park, Jaeheung; Lühr, Hermann; Michaelis, Ingo; Stolle, Claudia; Rauberg, Jan; Buchert, Stephan; Gill, Reine; Merayo, Jose M. G.; Brauer, Peter
Abstract In this study we investigate the three‐dimensional structure of low‐latitude plasma blobs using multi‐instrument and multisatellite observations of the Swarm constellation. During the early commissioning phase the Swarm satellites were flying at the same altitude with zonal separation of about 0.5∘ in geographic longitude. Electron density data from the three satellites constrain the blob morphology projected onto the horizontal plane. Magnetic field deflections around blobs, which originate from field‐aligned currents near the irregularity boundaries, constrain the blob structure projected onto the plane perpendicular to the ambient magnetic field. As the two constraints are given for two noncoplanar surfaces, we can get information on the three‐dimensional structure of blobs. Combined observation results suggest that blobs are contained within tilted shells of geomagnetic flux tubes, which are similar to the shell structure of equatorial plasma bubbles suggested by previous studies.